S.T.O.N.E. Score, Guy’s Score, and CROES Nomogram in Predicting Stone Clearance following Percutaneous Nephrolithotomy - Timilsina, Bhusan Raj; Pradhan, Sulav; Sah, Nirmal Prasad; Thapa, Ganesh; KC, Sudeep Raj (Journal of Bharatpur Hospital, 2025)
Background Percutaneous Nephrolithotomy (PCNL) is the standard treatment for large renal calculi. Several scoring systems have been developed to preoperatively predict its success. This study aims to compare the predictive accuracy of the Guy’s Stone Score (GSS), S.T.O.N.E. nephrolithometry, and the Clinical Research Office of the Endourological Society (CROES) nomogram for stone-free status after PCNL. Methods A single-center, cross-sectional study was conducted from February 2021 to August 2022, including 75 patients who underwent PCNL. Preoperative variables were used to calculate the three scores. Stone-free status was defined as residual fragments <4mm on post-operative CT. The predictive ability of each score was assessed using Receiver Operating Characteristic (ROC) curve analysis, with comparison of the Area Under the Curve (AUC). Statistical analysis was performed using EZR version 1.36. Results The overall stone-free rate was 60%. The mean S.T.O.N.E. and CROES scores were 7.0±1.1 and 269.6±50.4, respectively. The AUC for predicting stone-free status was 0.768 for GSS, 0.673 for S.T.O.N.E., and 0.786 for the CROES nomogram. All three scores were statistically significant predictors (p-value<0.05). However, pairwise comparison of the ROC curves revealed no statistically significant difference in predictive accuracy between the three systems (p-value>0.05 for all comparisons). Conclusions The Guy’s score, S.T.O.N.E. nephrolithometry, and CROES nomogram are all highly predictive of stone-free status following PCNL, providing a quick method for grading procedural complexity. No single scoring system demonstrated superior predictive value over the others, allowing for flexibility in their clinical application based on available imaging and surgeon preference.